Pertanggungjawaban Pidana bagi Pelaku Pembunuhan yang Mengidap Gangguan Jiwa Periodik : (Studi Kasus Putusan No.41/Pid.B/2020/PN End) - Geraldus Damansus Boro Sale; Karolus K. Medan; Aksi Sinurat (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
The purpose of this study is to find out about someone who has a mental disorder periodically committing an unlawful act, can be given legal responsibility for his actions, and the basis for the judge's considerations in sentencing the perpetrator of the crime of murder who has a mental disorder periodically. The type of research is normative legal research. The research data collection technique uses literature studies. The data will then be analyzed using qualitative analysis. The results of the study show that based on the theory of criminal responsibility, a person with a mental disorder cannot be punished because he is considered not to have the awareness and ability to be responsible or his actions, but there is a submission in the case of periodic mental disorders experienced by the defendant in the sentence, the legal status of the perpetrator does not immediately get a full element of forgiveness, in the audit the judge considered it worthy of being held criminally responsible because his actions had fulfilled the elements of criminal responsibility. The judge's decision ignored the conditions of the conversation with a history of periodic mental disorders showing weaknesses in aspects, legal certainty, benefits and protection of human rights, in contrast to the principles of legalization and violation of national law and imprisoning people who have a history or even are mentally ill does not provide benefits to the person himself.